IPTEK BAGI MASYARAKAT PEMBUDIDAYA IKAN HIAS AIR TAWAR KABUPATEN TULUNGAGUNG - Ekojono .; Dyah Ayu Irawati; Hari Kurnia Safitri; Anugrah Nur Rahmanto (Universitas Muhammadiyah Ponorogo, 2018)
Freshwater fish is one of the flagship of Tulungagung regency where freshwater fish are cultivated in ponds around the house. The main problems faced by two Partners in this program is the growth of fish are strongly influenced by water quality and water circulation conditions. While the problems in post-harvest is that when quarantine in the aquarium requires regulation of dissolved oxygen levels, circulation, and temperature. This community service activity using a science and technology for society approach (IbM). The method of implementation of this activity are: 1) providing counseling; 2) the installation of appropriate technology (TTG) to the two partners in the form of pond’s electricity management with setup installation of electrical system complete with backup generator; and 3) training on the use of TTG. The results of IbM's activities turned out to have a positive impact for freshwater fish farmers because it has decreased the number of fish mortality, which means increasing the income of the two partners.